Mifepristone potentiates etoposide toxicity in Hep G2 cells by modulating drug transport - Dostál, Z; Kosina, P; Mlejnek, P; Kikalová, K; Modrianský, M (Toxicology in vitro, 2019)
Etoposide is a well-known and widely used anticancer drug that displays several side effects. In addition, tumors often acquire resistance to this drug. Our aim is to develop a combination therapy that would augment toxicity of etoposide in malignant cells. Based on literature and our experiments, we selected mifepristone (RU486) as a potential supporting molecule that is able to enhance etoposide toxicity against cancer cells. All experiments were performed with Hep G2 cells, a well-known and described human hepatocellular carcinoma cell line. By using xCELLigence system, we demonstrated that mifepristone enhances toxicity of etoposide in a dose dependent manner with concomitant caspase-3 activity. We evaluated upregulation of Bax because mifepristone was demonstrated to modulate proapoptotic Bax protein expression. Our data show only weak and not statistically significant increase of Bax expression. On the other hand, we show that mifepristone increases etoposide toxicity via inhibition of ABC transporters, coupled with significant increase of intracellular etoposide concentration. In conclusion, we demonstrate that mifepristone has a synergistic effect with etoposide treatment in the Hep G2 cells and that the effect is related to ABC transporters inhibition.
Keywords: nádorové proteiny; mifepriston; viabilita buněk; bcl-2-Associated X Protein; Caspase 3; Antineoplastic Agents, Phytogenic; kaspasa 3; buňky Hep G2; ATP Binding Cassette Transporter, Subfamily G, Member 2; Cell Survival; xCELLigence; etoposid; Drug Synergism; P-glykoproteiny; protein X asociovaný s bcl-2; synergismus léků; Mifepristone; buňky K562; biologický transport; lidé; ABC transportér z rodiny G, člen 2; Humans; Hep G2 Cells; ABC transporters; Neoplasm Proteins; K562 Cells; ATP Binding Cassette Transporter, Subfamily B; fytogenní protinádorové látky; RU486; Hep G2 cells; Biological Transport; Etoposide